2011
DOI: 10.1007/s00894-011-1184-3
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-based 3-D pharmacophore generation and molecular docking of mTOR kinase inhibitors

Abstract: The 3-D structure of the human mTOR kinase domain was modeled based on the crystal structure of PI3Kγ using comparative modeling methods, and the ATP-binding site of mTOR was characterized. The mTOR kinase 3-D model structure is similar to the structure of the PI3Kγ kinase domain, and exhibits great similarity to PI3Kγ at the active site of the kinase. Pharmacophore generation, the docking of mTOR inhibitors, and molecular dynamics (MD) simulations of mTOR-inhibitor docked complexes were carried out in this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(40 reference statements)
4
12
0
Order By: Relevance
“…Distance analyses suggest that the hydrogen bond between 13 and the side chain of Val2240 is conserved during 10 ns MD simulations ( Figure S4a ). Previous studies demonstrated the hydrogen bond between inhibitor and Val2240 was necessary for mTOR inhibitory activity 23 24 25 , which was consistent with our analysis. The hydrogen bond between 13 and the carboxyl oxygen atom of Asp2195 is maintained for the first 5 ns in our simulations and occasionally disappears after 5 ns ( Figure S4b ), suggesting this hydrogen bond is not stable in water.…”
Section: Resultssupporting
confidence: 92%
“…Distance analyses suggest that the hydrogen bond between 13 and the side chain of Val2240 is conserved during 10 ns MD simulations ( Figure S4a ). Previous studies demonstrated the hydrogen bond between inhibitor and Val2240 was necessary for mTOR inhibitory activity 23 24 25 , which was consistent with our analysis. The hydrogen bond between 13 and the carboxyl oxygen atom of Asp2195 is maintained for the first 5 ns in our simulations and occasionally disappears after 5 ns ( Figure S4b ), suggesting this hydrogen bond is not stable in water.…”
Section: Resultssupporting
confidence: 92%
“…The models exhibit potential to predict inhibitors that are not included in the training set. Similar work was also performed by Karunakar Tanneeru and coworkers, which resulted in four features pharmacophore model (two hydrogen bond acceptors, a hydrophobic center and an aromatic feature) based on 27 ATP-competitive mTOR inhibitors [21]. A disadvantage of 3D-QSAR or SAR models for mTOR inhibitors is the use of a series of compounds based on solely scaffold.…”
Section: Introductionmentioning
confidence: 80%
“…A number of attempts have been done to construct a pharmacophore model for various serine–threonine kinase inhibitors. For example, pharmacophore for STPK inhibitors of tuberculosis , for mTor kinase inhibitors , for Aurora B inhibitors , for Aurora A inhibitors and for B‐Raf inhibitors was developed. All these works were devoted to selected kinase of serine–threonine family, but we surmised that there are a number of common features of all serine–threonine inhibitors so it would be possible to construct a general pharmacophore model which subsequently could be optimized for specific kinds of serine–threonine kinase.…”
Section: Some Results Of General Ser/thr Pharmacophore Application Tomentioning
confidence: 99%